2011
DOI: 10.1111/j.1365-2109.2011.02844.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of the nutritive value of the variegated grasshopper (Zonocerus variegatus L.) for African catfish Clarias gariepinus (Burchell. 1822) fingerlings

Abstract: A preliminary feeding trial was conducted to evaluate the nutritive value of adult variegated grasshopper (Zonocerus variegatus) meal (VGM) as a replacement for ¢sh meal in the diets of Clarias gariepinus ¢ngerlings. Proximate analysis result showed that VGM had 61.50% crude protein, 6.87% crude lipid, 27.33 NFE and 9.35% chitin. Five isonitrogenous (30%) and isoenergetic (18.42 MJ kg À 1 ) diets were formulated in whichVGM progressively replaced ¢shmeal at ¢ve inclusion levels (0%, 25%, 50%, 75% and 100%). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 36 publications
7
69
1
3
Order By: Relevance
“…Whereas, published reports on BSFL meal as an alternative of fish meal are extremely few, but has been increasing recently (Cummins et al 2017). Our results are in consistence with those of previous studies, suggesting an optimum fish meal replacement level of 20-50% using insect meal (Wing-Keong et al 2001;StHilaire et al 2007b;Alegbeleye et al 2002;Cummins et al 2017) in different aquaculture species. Similar to our observation, these aforementioned studies also reported the limitations in replacing fish meal beyond 50% of diet using insect meal.…”
Section: Discussionsupporting
confidence: 81%
“…Whereas, published reports on BSFL meal as an alternative of fish meal are extremely few, but has been increasing recently (Cummins et al 2017). Our results are in consistence with those of previous studies, suggesting an optimum fish meal replacement level of 20-50% using insect meal (Wing-Keong et al 2001;StHilaire et al 2007b;Alegbeleye et al 2002;Cummins et al 2017) in different aquaculture species. Similar to our observation, these aforementioned studies also reported the limitations in replacing fish meal beyond 50% of diet using insect meal.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding fish, some trials have been carried out with various fish species to evaluate the use of diets containing different insect meals, often used as FM substitutes (Fasakin et al, 2003;St-Hilaire et al, 2007b;Sealey et al, 2011;Alegbeleye et al, 2012;Kroeckel et al, 2012;Oso and Iwalaye, 2014;Roncarati et al, 2015). The results of these trials confirm the possibility of insect meals inclusion in aquaculture feeds, even though there could be some limits related to both insect and fish species (Henry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…High prices of FM and increasing demand of aquaculture production have led to the establishment of research in insect protein for aquaculture and livestock Henry et al 2015). Insects meal such as grasshopper meal (Zonocerus variegatus) (Alegbeleye et al 2012), termites meal (Macrotermes spp.) (Sogbesan and Ugwumba 2008), superworm meal (Zophobas Mario) (Jabir et al 2012), mealworm (Tenebrio molitor) (Gasco et al 2016) as well as molluscs such as garden snail (Sogbesan et al 2006) and plants feedstuff (Muin et al 2015) have been identified as successful alternatives for FM replacement.…”
Section: Introductionmentioning
confidence: 99%